The Manufacture des meubles de la couronne aux Gobelins under Louis XIV a social, political, and cultural history - Knothe, Florian (Brepols, 2016)
The cultural importance, dependencies and mechanics of manufacture in Europe prior to the Industrial Revolution are understudied areas of research. In the case of French royal manufacture during the ancien régime, art-historical interest first awakened in the latter half of the nineteenth century with the publication of several descriptive texts that made archival sources available to a wider public. This volume on the Manufacture royale des meubles de la couronne aux Gobelins examines the current state of research on the royal workshops and indicates the manner by which this research can both extend and challenge the prevailing trends in the historiography of the Gobelins.0
Keywords: Ludwig -- XIV. -- Frankreich, König -- 1638-1715; Manufacture Nationale des Gobelins -- Paris; Geschichte 1650-1715; Silber; Bildteppich; Möbel; Höfische Kunst; Hochschulschrift